Three-dimensional evaluation of treatment results of the Alt-RAMEC and facemask protocol in growing patients - YILMAZ, HANİFE NURAY (URBAN & VOGEL, 2020)
Purpose The aim of this retrospective study was to evaluate the skeletal, dental, and soft tissue effects of the alternating rapid maxillary expansions and constrictions (Alt-RAMEC) protocol combined with a facemask in prepubertal patients. Methods The study group (mean age 9.74 +/- 1.46 years) consisted of 20 patients with class III malocclusion characterized by maxillary retrognathism. They were treated with a facemask for 7 months following a 9-week Alt-RAMEC protocol. Cone-beam computed tomography (CBCT) records and three-dimensional (3D) photographs taken before (T0) and after the protraction and retention period (T1) were evaluated. The study group was compared with a well-matched control group of 16 untreated patients (mean age 9.44 +/- 0.79 years) with the same malocclusion. The records for the control group included cephalometric radiographs and 3D photographs. Results In the study group, significant forward movements of A point (3.49 mm), nasal (2.91 mm) and zygomatic bones were achieved. Intermolar, internasal, and interzygomatic widths increased. Soft tissue points followed the hard tissue movements, apart from b and pog. In the control group, A (0.97 mm), B (1.69 mm), Pog, and b points presented forward movement. Significant differences were found regarding the forward movement of the maxilla between the groups. Conclusion The Alt-RAMEC/facemask protocol was effective not only in the maxillary region but also in the midface.
Keywords: Retrognathia; Cone-beam computed tomography; Malocclusion; Angle class III; Maxillary protraction; 3dMDface system; RAPID MAXILLARY EXPANSION; PROTRACTION